Moderate Red Wine Consumption Increases the Expression of Longevity-Associated Genes in Controlled Human Populations and Extends Lifespan in Drosophila melanogaster - Juan Gambini; Lucia Gimeno-Mallench; Gloria Olaso-Gonzalez; Angela Mastaloudis; Maret G. Traber; Daniel Monleón; Consuelo Borrás; Jose Viña (Antioxidants, 2021)
The beneficial effects of moderate red wine consumption on cardiovascular health are well known. The composition of red wine includes several compounds, such as the phytoestrogen resveratrol, that exert these beneficial effects, although not all the mechanisms by which they act are known. Our aim was to study the effect of red wine consumption on longevity-related genes in controlled human populations, such as cloistered nuns. We found that the expression of catalase, manganese-superoxide dismutase, Sirt1, and p53 was increased in peripheral blood mononuclear cells after 14 days of moderate red wine consumption. This increase was accompanied by an enhanced metabolic wellness: fatty acids, cholesterol, branched chain amino acids (isoleucine and leucine), ketone bodies (acetoacetate), bacterial co-metabolites (trimethylamine), and cellular antioxidants (taurine) contributed to a change in metabolic profile after moderate red wine consumption by the nuns. No serious unwanted side effects were observed. Finally, we tested the effect of moderate red wine consumption on longevity in a controlled animal population, such as D. melanogaster, and found that it increased average life span by 7%. In conclusion, moderate red wine consumption increases the expression of key longevity-related genes and improves metabolic health in humans and increases longevity in flies.